1982
DOI: 10.1104/pp.70.3.662
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Spin Labels in Oat Leaf Protoplasts

Abstract: An assay based on light-mediated oxidation was used to determine whether specific spin labels were partitioned throughout the protoplast or retained in the plasmalemma of Avena sativa L. cv. Garry and Park. Many classes of spin label were tested, including phospholipids, fatty acid, fatty acid methyl ester, maleimide, iodoacetamide, short chain hydrocarbon, androstane, 2,2,6,6-tetramethyl-4-aminopiperidinooxyl (TEMPAMINE) and 2,2,6,6-tetramethylpiperdinooxyl (TEMPO). All except the phosphotidylcholine spin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

1982
1982
1989
1989

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…Our data do not address the question of which membrane, if any, is the most affected by cercosporin, because fatty acid spin labels such as I(12,3) and I(1,14) partition throughout all of the membranes of the protoplast and give a composite spectrum (2). The data do show, however, that the increased membrane microviscosity caused by cercosporin is not restricted to either the surface or center of the membrane bilayer.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…Our data do not address the question of which membrane, if any, is the most affected by cercosporin, because fatty acid spin labels such as I(12,3) and I(1,14) partition throughout all of the membranes of the protoplast and give a composite spectrum (2). The data do show, however, that the increased membrane microviscosity caused by cercosporin is not restricted to either the surface or center of the membrane bilayer.…”
Section: Discussioncontrasting
confidence: 38%
“…For studies on membrane phase transformation temperatures, spectra were run at 1 to 2°C intervals, and the data were analyzed by linear regression. In contrast to protoplasts from mesophyll cells (2), protoplasts from suspension cultures did not Plant Physiol. Vol.…”
mentioning
confidence: 98%
“…Using ESR technique, Singh and Miller (17) demonstrated that isolated plant cells may undergo an irreversible reorganization of lipid bilayers to a less ordered amorphous state after freezing at a lethal temperature. However, as pointed out by Briggs et aL (6), when intact or isolated protoplasts are used for ESR studies, problems remain as to whether or not the fatty acid spin labels were selective for the plasma membranes. They showed that most of the labels were partitioned throughout the cells and, thus, the ESR signals reported an average from every membrane in the cells.…”
mentioning
confidence: 99%